Application Control Effectiveness in Cloud-Based Accounting Software: Comparative Analysis of Mekari and Xero - Salim, Cornelius Jevon Tirta; Antonio, Gregorius Rudy (ESENSI: Jurnal Manajemen Bisnis, 2025)
This study evaluates application control effectiveness in two prominent cloud-based accounting platforms, Mekari Jurnal ID and Xero, through systematic black box testing of revenue cycle controls. Employing a qualitative explanatory research design, the investigation examined input controls (missing data checks, numeric-alphabetic validation, limit checks, range checks, validity checks, sign checks, sequence checks) and output controls (transaction logging, report accuracy) across quotation, sales order, and invoice modules. Testing was conducted between October 2024 and January 2025 using trial accounts with comprehensive working paper documentation. The findings revealed significant control weaknesses in both platforms including inadequate field validation permitting single-character entries, insufficient inventory limit enforcement enabling overselling, inconsistent discount percentage validation, absence of sequential document numbering protocols, and deficient transaction logging capabilities in Mekari Jurnal ID. Both platforms demonstrated accurate master data validation and sign check controls but failed to enforce sequence integrity or prevent commercially unreasonable value entries. Comparative analysis indicated that Mekari Jurnal ID exhibited stronger stage-based preventive controls while Xero demonstrated superior transaction logging granularity. The research contributes empirical evidence to the limited literature on cloud-based accounting controls and provides actionable recommendations for software developers, business users, accounting professionals, and auditors to enhance internal control effectiveness in cloud computing environments.